Perbedaan Eksistensi Penggunaan Bahasa Indonesia antara Generasi Milenial dan Generasi Z - Wediasti, Welti; Hiasa, Fina (Jurnal Korpus, 2025)
This study discusses the differences in the existence of the use of Indonesian between the Millennial Generation and Generation Z. Along with the development of technology and globalization, the communication patterns of these two generations have undergone significant changes, especially in terms of language use so that it can be accepted by the two different age groups so that it can detect the potential for a shift in the use of Indonesian which if left unchecked does not rule out the possibility of the extinction of the use of Indonesian. This study aims to analyze how the differences in the use of Indonesian between the two generations, the factors that influence it, and its impact on the sustainability of the national language so that it can develop strategies for preserving Indonesian, both academically and in community life. Therefore, it can be said that this study can provide an important contribution in efforts to preserve and develop Indonesian as the national language and symbol of the nation. The research method used is a mixed approach (mix methods) between qualitative and quantitative approaches. Data were collected through interviews, questionnaires, and social media analysis to identify patterns of Indonesian use by each generation. The results of the study show that the Millennial Generation tends to maintain more formal Indonesian language rules in professional and everyday communication, while Generation Z uses more mixed languages ​​(code-mixing and code-switching), especially with foreign languages ​​such as English in digital communication. The main factors influencing these differences are the social environment, the development of digital technology, and exposure to global culture. In addition, social media has an important role in shaping the language habits of Generation Z which are more flexible and expressive than the Millennial Generation. Nevertheless, the existence of Indonesian remains strong because it is still the main language in official and academic communication. This study concludes that the differences in the existence of language use between the Millennial Generation and Generation Z in language use patterns do not necessarily threaten the existence of Indonesian, but rather indicate the adaptation of language to the dynamics of the times. Therefore, educational efforts and linguistic policies are needed that can maintain the sustainability of Indonesian without inhibiting creativity and innovation in communication.